KOMODIFIKASI KEARIFAN LOKAL DI BIDANG KESEHATAN SEBAGAI DAYA TARIK WELLNESS TOURISM DI UBUD - Suteja, I Wayan; Ardika, I Wayan; Pujaastawa, Ida Bagus Gde (Jurnal Master Pariwisata (JUMPA); Volume 05, Nomor 01, July 2018, 2018)
This study discusses the commodification of local wisdom in health sector as the attraction of wellness tourism in Ubud Tourism Area. This research addresses the problem about the forms of commodification of local wisdom in health sector as an attraction of wellness tourism in Ubud Tourism Area. The method used to analyse the data is descriptive qualitative method with qualitative data. Types of data used are primary and secondary data with data collection techniques such as in-depth interviews, observations, documentations and literature studies. Based on the results of this study it can be explained that the development of commodification of local wisdom in health sector as a health tourism attraction in the Ubud Tourism Area occurs in the form of commercialisation, profanisasi and modernisation. Commercialisation is identified in the form of place arrangement, product packaging and marketing. Then the profanisation occurs causes the decline in the sacred value of local wisdom into economic-oriented activities. Modernisation also has changed the local wisdom into modernised products.